Breastfeeding mothers with COVID-19 infection: a case series - Augusto Pereira; Sara Cruz-Melguizo; Maria Adrien; Lucia Fuentes; Eugenia Marin; Azul Forti; Tirso Perez-Medina (BMC, 2020)
Abstract Background The first reports of the Chinese experience in the management of newborns of mothers with SARS-CoV 2 infection did not recommend mother-baby contact or breastfeeding. At present, the most important International Societies, such as WHO and UNICEF, promote breastfeeding and mother-baby contact as long as adequate measures to control COVID-19 infection are followed. In cases where maternal general health conditions impede direct breastfeeding or in cases of separation between mother and baby, health organizations encourage and support expressing milk and safely providing it to the infants. Methods A series of 22 case studies of newborns to mothers with COVID-19 infection from March 14th to April 14th, 2020 was conducted. Mothers and newborns were followed for a median period of 1.8 consecutive months. Results Out of 22 mothers, 20 (90.9%) chose to breastfeed their babies during hospital admission. Timely initiation and skin to skin contact at delivery room was performed in 54.5 and 59.1%, respectively. Eighty two percent of newborns to mothers with COVID-19 were fed with breast milk after 1 month, decreasing to 77% at 1.8 months. Six of 22 (37.5%) mothers with COVID-19 required transitory complementary feeding until exclusive breastfeeding was achieved. During follow-up period, there were no major complications, and no neonates were infected during breastfeeding. Conclusions Our experience shows that breastfeeding in newborns of mothers with COVID-19 is safe with the adequate infection control measures to avoid mother-baby contagion. Supplementing feeding with pasteurized donor human milk or infant formula may be effective, until exclusive breastfeeding is achieved.